Detergent solubilization of bovine erythrocytes. Comparison between the insoluble material and the intact membrane - Rodi, Pablo Marcelo (2006)
Early works have shown that when biomembranes are extracted with the non-ionic detergent Triton X-100 at 4°C, only a subset of the components is solubilized. The aim of this paper was to investigate the solubilization of a cell membrane at different Triton concentrations, and to compare the lipid composition and acyl chain order/mobility of the insoluble material with those of the original membrane. We choose bovine erythrocytes, because they have an uncommon composition, as they have a huge amount of sphingomyelin and phosphatidylcholine is almost absent. We determined the degree of order/mobility of the lipid acyl chains by EPR spectroscopy, using liposoluble spin labels. Incubation of bovine erythrocytes with increasing Triton X-100 concentrations yields decreasing amounts of insoluble material which is enriched in sphingomyelin and depleted in cholesterol. Complete lipid solubilization is achieved at a detergent/lipid ratio of about 60, which is much higher than the values reported for human erythrocytes, but is in line with results obtained in model systems. An insoluble pellet is still obtained at higher Triton concentrations, which seems to consist mainly of protein. A very high correlation is found between lipid chain mobility restrictions and sphingomyelin content in the lipid structures. The human erythrocyte membrane also fits well in this correlation, suggesting a significant role of sphingomyelin in determining acyl chain organization. The analogies and differences between our insoluble material and the detergent-resistant membranes (DRM) are discussed.